2003
DOI: 10.1212/01.wnl.0000063304.88470.d9
|View full text |Cite
|
Sign up to set email alerts
|

Lamotrigine for HIV-associated painful sensory neuropathies

Abstract: Lamotrigine was well-tolerated and effective for HIV-associated neuropathic pain in patients receiving neurotoxic antiretroviral therapy. Additional research is warranted to understand the differing response among patients receiving neurotoxic antiretroviral therapy compared with those not receiving neurotoxic antiretroviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(94 citation statements)
references
References 26 publications
1
88
0
5
Order By: Relevance
“…However, a notable randomized, double-blind, placebo-controlled eight-week study in patients with various neuropathic pain syndromes at doses of 200 mg/day showed no significant benefit for lamotrigine. [115][116][117][118][119][120] …”
Section: Lamotriginementioning
confidence: 99%
“…However, a notable randomized, double-blind, placebo-controlled eight-week study in patients with various neuropathic pain syndromes at doses of 200 mg/day showed no significant benefit for lamotrigine. [115][116][117][118][119][120] …”
Section: Lamotriginementioning
confidence: 99%
“…However, a subsequent randomized controlled trial that tested this higher dose in HIV neuropathy patients was negative. 32 Moreover, the high rate of discontinuation of therapy in this study (higher in the lamotrigine arm when compared with placebo) would indicate that a higher dose would be less well tolerated. Therefore, it appears unlikely that the lack of efficacy noted in this study can be attributed to suboptimal dosing.…”
Section: Discussionmentioning
confidence: 83%
“…27 A single high-concentration capsaicin patches has shown sustained 12 weeks of pain reduction in HIV-associated polyneuropathy. 28 Randomized controlled trials have demonstrated positive results for cannabis smoking, however, administration of cannabis smoking for a long term has high addictive potential and associated health risk.…”
Section: Hiv Associated Polyneuropathymentioning
confidence: 99%